Economic feasibility of owning of a small wind generator - Hopkins, Mark; Pahwa, Anil (Kansas State University, 2009)
People looking for solutions to global warming and rising energy costs may see solar and wind energy as a high-risk low-reward solution. The aim of this research is to develop a Monte-Carlo based method for determining an expected amount of energy production for these types of systems and to test this method on one type of system.
Keywords: Solar energy; Wind energy; Energy costs; Monte-Carlo methods